'Manly' and effeminate, wretched and whole: formulating gender identity through stills and film. Issue 3 (2nd October 2021) - Gil-Glazer, Ya'ara
Abstract: This case study discusses a personal-political process of formulating gender identity in heteronormalized academic spaces through photography and film. This process, by a former high school art student, presently an undergraduate film student in Israel, reflects interfaces between critical visual literacy and critical emancipatory pedagogy. In analyzing this process, Bell hooks' concept of the oppositional gaze is expanded and applied to examine the artworks and their public presentation as a site of resistance for LGBTQs in heteronormative academic spaces, in the context of the Israeli myth of masculinity.